Synthesis of Polyurethane/Hyaluronic acid/Royal Jelly Electrospun Scaffold and Evaluating its Properties for Wound Healing - Mehdi Movahedi; Azadeh Asefnejad; Mohammad Rafienia; Mohammad Taghi Khorasani (Journal of Mazandaran University of Medical Sciences, 2021)
Background and purpose: Studies showed that biocompatible and biodegradable materials in tissue engineering can be used to heal wounds. The aim of this study was to fabricate polyurethane/royal jelly/hyaluronic acid scaffold with suitable biological properties for wound healing using electrospinning method. Materials and methods: In this applied experimental study, to make a nanofiber scaffold, 10% by weight/weight of polyurethane was dissolved at room temperature for 2 hours. Then, royal jelly (in different ratios) and hyaluronic acid (1% by w/w) were added to the polyurethane solution and electrospinning was performed. For biological evaluation, in vitro and finally in vivo analyses were performed. Results: Polyurethane scaffold containing 1% w/w of hyaluronic acid and 6% w/w of royal jelly was fabricated by electrospinning method. Scanning electron microscope images showed bead-free uniform fibers. The diameter of scaffold fibers was 546.8 nm. The contact angle of the scaffold was 51.610 indicating the hydrophilic properties of the scaffold. Moreover, the scaffold did not show any toxicity. Royal jelly improved cell proliferation and increased the cell adhesion of the scaffold. In the in vivo analysis, the wound healing process in the presence of the prepared scaffold was 92.21% after 14 days. Conclusion: Electrospun polyurethane scaffold containing 1% w/w of hyaluronic acid and 6% w/w of royal jelly was studied for the first time and in vitro and in vivo studies showed that this scaffold can be a suitable candidate in skin tissue engineering and wound healing.